Genome-Wide Identification of Maize Aquaporin and Functional Analysis During Seed Germination and Seedling Establishment - Su, Yingchun; Liu, Zhonghao; Sun, Jiahui; Wu, Chenglai; Li, Yan; Zhang, Chunqing; Zhao, Linmao (Frontiers in Plant Science, 2022)
Water uptake facilitates the initiation of seed germination. It is presumed that aquaporin (AQP)-mediated water inflow contributes to seed germination, but the genetic evidence is still lacking. This study aimed at genome-wide identification of ZmAQPs and further determined the physiological functions. Following a comprehensive search, a total of 41 ZmAQPs were identified according to the latest genome database. Through bioinformatic approaches, the physicochemical characteristics, phylogenetic relationships, and structural features of ZmAQPs were analyzed. The gene expression analysis of 20 high-resolution and multi-tissues samples showed that ZmAQPs had distinct spatiotemporal and tissue-specific expression profiles during seed germination and early seedling development. We then focused on the aquaporin of maize tonoplast intrinsic protein 3 (ZmTIP3), which is specifically expressed in germinating seed. A mutant zmtip3-1 with disruption of the ZmTIP3-1 gene showed shorter shoot and root length, and decreased seedling dry weight compared with the control (W22). The result revealed that ZmTIP3-1 improved the absolute content of seed protein and promoted storage reserves mobilization, suggesting that ZmTIP3 may be a positive regulator of seed vigor. This work provides valuable clues for understanding the function and possible regulatory mechanism of ZmAQPs in seed germination and seedling growth.